THE ROLE OF THE SYSTEMATIC APPROACH IN DETERMINING THE RELIABILITY OF TECHNICAL SYSTEMS IN A TRANSPORT LOGISTICS SYSTEMS: THE ROLE OF THE SYSTEMATIC APPROACH IN DETERMINING THE RELIABILITY OF TECHNICAL SYSTEMS IN A TRANSPORT LOGISTICS SYSTEMS - Nedev, Nikolay (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This publication defines the scope of inspections of railway facilities and devices, as well as the methods for recording results and taking action to remedy malfunctions. The re-liability of systems in transport logistics is key to the efficiency and safety of processes. It ensures that all components of the system work smoothly and predictably.